A Study of Tense Variation in Advertisements (مجلة ديالى للبحوث الانسانية, 2025)
Advertisements have become gradually popular. People are exposed to a great number of advertising messages everyday. The aim of advertisements is to persuade consumers to think in a determined textual manner and act in order to promote sales of particular products, goods and services. Advertisements use a range of manipulative language devices in order to catch attention, convey messages and persuade the consumer. The paper aims at analyzing and describing English tense system used in advertising. It tries to find out whether tense as a linguistic syntactic device contributes in the persuasion goal of advertising. Therefore, the paper examines which types of tense are frequently used along with the functions they fulfill. The data in this study is 334 advertisements; these were taken from various English international magazines. The data collection was analyzed from a syntactic point of view. The findings show that the present simple tense is the most frequent type used in advertisements under study, while the past simple tense is the least frequent one, while there are other tense forms that have never been used. Furthermore, the results of analysis show that there seems to be a relationship between tense choice and functions of advertising, i.e., between the basic meanings and uses of tense choice and the persuasive functions. The importance of employing syntactic devices like tenses in creating an effective language helps to convey advertising intended messages. The study helps clarify relations between verb form and persuasion functions.